2020
DOI: 10.3389/fmed.2020.598438
|View full text |Cite
|
Sign up to set email alerts
|

Management of Asymptomatic Sporadic Nonfunctioning Pancreatic Neuroendocrine Neoplasms (ASPEN) ≤2 cm: Study Protocol for a Prospective Observational Study

Abstract: Introduction: The optimal treatment for small, asymptomatic, nonfunctioning pancreatic neuroendocrine neoplasms (NF-PanNEN) is still controversial. European Neuroendocrine Tumor Society (ENETS) guidelines recommend a watchful strategy for asymptomatic NF-PanNEN <2 cm of diameter. Several retrospective series demonstrated that a non-operative management is safe and feasible, but no prospective studies are available. Aim of the ASPEN study is to evaluate the optimal management of asymptomatic NF-PanNEN ≤2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…Surgical resection is indicated in cases of large tumors, rapidly growing or poorly differentiated Grade 3 PNEC (14). For welldifferentiated, Grade 1 and 2 nonfunctional PNETs <2 cm and growing <0.5 cm during 6-12 month time frame conservative management is recommended with follow up imaging (CT or MRI); however, prospective studies are needed to further define surgical intervention, as early removal of this lesions may be associated with better long term outcomes (24,28). The 5-year progression free survival for incidentally diagnosed nonfunctional PNETs is 86%, compared to 59% in symptomatic functional tumors (26).…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection is indicated in cases of large tumors, rapidly growing or poorly differentiated Grade 3 PNEC (14). For welldifferentiated, Grade 1 and 2 nonfunctional PNETs <2 cm and growing <0.5 cm during 6-12 month time frame conservative management is recommended with follow up imaging (CT or MRI); however, prospective studies are needed to further define surgical intervention, as early removal of this lesions may be associated with better long term outcomes (24,28). The 5-year progression free survival for incidentally diagnosed nonfunctional PNETs is 86%, compared to 59% in symptomatic functional tumors (26).…”
Section: Introductionmentioning
confidence: 99%
“…The most typical example is represented by pancreatic NENs. Considering that, in the most recent decade, we observed a dramatic increase in the diagnosis of small, incidentally discovered, nonfunctioning pancreatic NENs [3,5], and a clear relationship between the tumor diameter and the risk of malignancy and recurrence has been reported [18], ENET guidelines started to recommend a "wait and see" approach for small asymptomatic non-functioning pancreatic NENs [12], and a European trial is currently ongoing [19]. Furthermore, endoscopic ablative technologies may also be utilized in patients with pancreatic NENs not suitable for surgery or who refused the surgical approach.…”
mentioning
confidence: 99%
“…Several series and a review published by Partelli S et al in 2017 [ 19 ] suggested that patients with incidental tumors less than 2 cm in diameter experienced a limited risk of tumor recurrence and were all alive at 5 years. The European Neuroendocrine Tumor Society (ENETS) guidelines then proposed a “watch and wait” policy in asymptomatic patients with sporadic < 2 cm low-grade (G1) p-NETs [ 20 ]. Histopathological confirmation is mandatory in this situation [ 21 ], but no consensus has emerged regarding the follow-up protocol.…”
Section: Multimodal Management Of Localized Diseasementioning
confidence: 99%